1987
DOI: 10.1063/1.452510
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption and thermal decomposition of water on clean and oxygen-predosed Al(111)

Abstract: The adsorption of water on both clean and oxygen-predosed Al(111) has been studied by vibrational spectroscopy using electron energy loss spectroscopy (EELS). At 130 K, adsorption on either surface is competitively associative and dissociative. The dominant dissociation product is a hydroxyl species. On the clean surface, adsorption is predominantly molecular, while in the presence of oxygen, adsorption is predominantly dissociative. In contrast to the low temperature behavior, adsorption of water on clean Al(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 62 publications
5
51
0
Order By: Relevance
“…From the PDOS analysis, it is clear that the bonding between the O and metal surface is mainly ionic. [17] suggested that adsorption is predominantly molecular on the clean surface at low temperature, while in the presence of oxygen, adsorption is predominantly dissociative. They also found that the production of adsorbed hydroxyl species from water reaches a maximum at 250 K on the clean surface and at 350 K on the oxygen-predosed surface.…”
Section: Reaction Mechanism Of H 2 O Dissociationmentioning
confidence: 98%
“…From the PDOS analysis, it is clear that the bonding between the O and metal surface is mainly ionic. [17] suggested that adsorption is predominantly molecular on the clean surface at low temperature, while in the presence of oxygen, adsorption is predominantly dissociative. They also found that the production of adsorbed hydroxyl species from water reaches a maximum at 250 K on the clean surface and at 350 K on the oxygen-predosed surface.…”
Section: Reaction Mechanism Of H 2 O Dissociationmentioning
confidence: 98%
“…This characteristic of H 2 O is well known from UHV studies of oxidation of Al and its alloys (Eberhardt and Kunz 1978, Netzer and Madey 1983, Crowell et al 1987, McConville et al 1987, Pansoy-Hjelvik et al 1998). There, the e ect is related to enhanced formation of oxides which contain OH groups, such as AlO(OH) or Al(OH) 3 (Textor and Grauer 1983).…”
Section: Variable Angle Methodsmentioning
confidence: 62%
“…While the residual gases in the chamber consisted predominantly of H 2 O and H 2 , molecular hydrogen is expected to be inconsequential at the Cu surface due to a dissociative adsorption barrier 32,33 of ϳ1 eV, while the residual water vapor absorbs readily with binding energies of up to a few electron volts. 18,[34][35][36] The formation of H − , therefore, is associated primarily with the re-adsorption of residual water vapor on the copper surface.…”
Section: Experimental Techniquesmentioning
confidence: 99%